Preliminary validation of two math screening tools to identify gifted students in grades 3–5 in Jordan - Abu-Hamour, Bashir; Al Hmouz, Hanan (Frontiers in Psychology, 2025)
IntroductionEarly screening for mathematically gifted students (MGSs) in Jordan and other Arab countries is limited, posing challenges in identifying and providing appropriate educational services. This study evaluates the validity and reliability of the Arabiya Calculation Test and Math Curriculum-Based Measurement (M-CBM) as tools for effectively screening and supporting MGSs in inclusive education settings. These tools were developed based on the Jordanian curriculum and international assessment tools and require further validation for use in other Arabic-speaking countries.MethodsA quantitative research design was employed, using the Arabiya Calculation Test and M-CBM to assess 78 MGSs in grades 3, 4, and 5 across three schools in Jordan. The tools’ reliability and validity were evaluated, with findings specifically limited to these grades. Performance differences among students and correlations between the two measures were analyzed.ResultsThe findings demonstrated that both the Arabiya Calculation Test and M-CBM are valid and reliable tools for identifying MGSs. These tools effectively differentiated performance across grades 3, 4, and 5. In addition, the significant correlation between these two measures supported their validity in identifying gifted students.DiscussionThe results have important implications for educational practice and policy in Jordan and similar Arab countries. Accurate identification of gifted students may facilitate tailored instruction and enrichment programs, improving the experience of inclusive education. These assessment tools offer the potential to identify gifted students early and meet their needs within an inclusive school environment.